Short-interval second ejaculation improves sperm quality, blastocyst formation in oligoasthenozoospermic males in ICSI cycles: a time-lapse sibling oocytes study - Li, Yaoxuan; Wang, Shikai; Li, Dawen; Huang, Yueyue; Liu, Haifang; Zhang, Xiaohui; Qin, Jie; Mao, Xianbao; Li, Zhengda; Chen, Liangshi; Wei, Pingpin; Shi, Wen; et al. (Frontiers in Endocrinology, 2023)
Background: Does short-interval second ejaculation improve sperm quality, embryo development and clinical outcomes for oligoasthenozoospermia males received intracytoplasmic sperm injection (ICSI) treatment? Methods: All enrolled male patients underwent short-interval secondary ejaculation on the day of oocyte retrieval, and 786 sibling MII oocytes from 67 cycles were equally divided into two groups based on whether the injected spermatozoons originated from the first or second ejaculation. Semen parameters, embryo development efficiency, morphokinetic parameters and clinical outcomes were compared between the two groups to assess the efficiency and clinical value of short-interval second ejaculation in ICSI cycles.Results: Short-interval second ejaculation significantly improved sperm motility, normal morphological rate, and sperm DNA integrity both before and after sperm swim-up. The high-quality blastocyst rate (24.79% versus 14.67%), available blastocyst rate (57.56% versus 48.44%), and oocyte utilization rate (52.93% versus 45.29%) were significantly higher in the second ejaculation group (P<0.05). The clinical pregnancy rate (59.09% versus 47.37%), implantation rate (42.11% versus 32.35%) and live birth rate (40.91% versus 31.58%) were higher in the second ejaculation group, but the differences were not significant (P>0.05). Time-lapse analysis showed that morphokinetic time points after the 7-cell stage were earlier in the second ejaculation group but without a significant difference (P>0.05), and abnormal embryo cleavage patterns between the two groups were not significantly different (P>0.05).Conclusions: Short-interval second ejaculation significantly improves sperm quality in oligoasthenozoospermic males, and is beneficial for blastocyst formation efficiency in ICSI cycles. This study suggested a non-invasive and simple but effective strategy for improving ICSI treatment outcomes.